High-Throughput RNA Sequencing Reveals the Effect of NB-UVB Phototherapy on Major Inflammatory Molecules of Lesional Psoriasis - Vacharanukrauh P (Dove Medical Press, 2021)
Pinyadapat Vacharanukrauh,1 Jitlada Meephansan,1 Pattarin Tangtanatakul,2 Wipasiri Soonthornchai,3 Jongkonnee Wongpiyabovorn,4 Onsiri Serirat,5 Mayumi Komine6 1Division of Dermatology, Chulabhorn International College of Medicine, Thammasat University, Pathum Thani, 12120, Thailand; 2Department of Transfusion Medicine and Clinical Microbiology, Faculty of Allied Health Sciences, Chulalongkorn University, Bangkok, 10330, Thailand; 3Demonstration School, University of Phayao, Phayao, 56000, Thailand; 4Division of Immunology, Department of Microbiology, Faculty of Medicine, Center of Excellence in Immunology and Immune Mediated Diseases, Chulalongkorn University, Bangkok, 10330, Thailand; 5Division of Dermatology, Department of Medicine, Rajavithi Hospital, Ministry of Public Health, Bangkok, 10400, Thailand; 6Department of Dermatology, Jichi Medical University, Tochigi, JapanCorrespondence: Jitlada MeephansanDivision of Dermatology, Chulabhorn International College of Medicine, Thammasat University, Rangsit Campus, Klong Luang, Pathum Thani, 12120, ThailandTel +662564-4444, ext.1535Fax +662564-4440, ext.7594Email kae_mdcu@yahoo.comObjective: To identify the narrowband ultraviolet B (NB-UVB)-induced molecular mechanisms that may account for their anti-inflammatory efficacy, gene expression and transcriptome profiling, which were performed using advanced molecular techniques.Methods: This research was conducted on patients with moderate-to-severe plaque-type psoriasis who received NB-UVB treatment. RNA sequencing (RNA-Seq) was conducted to assay the transcriptomes and identify the differentially expressed transcripts that had been enriched during the major pathway analysis.Results: Clinical improvement of psoriasis by NB-UVB therapy is linked to the suppression of the “immunological signaling pathways” and “cell cycle regulatory, growth and proliferation pathways” which are critical to the pathogenesis of the disease. In addition, these results were further substantiated by demonstrating that NB-UVB therapy has a significant effect on keratinocyte differentiation and affects the regulation of genes and inflammatory mediators that are related to cell proliferation and apoptosis. Moreover, NB-UVB phototherapy is also involved with the downregulation of toll-like receptors signaling in lesional psoriasis.Conclusion: NB-UVB is an effective treatment for psoriasis. Our study supports the conclusion that the clinical effectiveness of NB-UVB therapy is based on the suppression of a broad range of inflammatory signaling pathways, gene expression of inflammatory cytokines and increased expressions of anti-inflammatory signaling pathways in psoriatic skin. This is the first study that applied advanced molecular techniques to investigate phototherapy as a new key to unlock genetic knowledge and create novel information. Ultimately, the goal is to increase medical knowledge and improve the patient care of psoriasis.Keywords: psoriasis, pathogenesis, inflammation, NB-UVB, high-throughput RNA-sequencing, Inflammation, gene, translational study, chronic skin disease, UVB irradiation